Student Adjustment in Undertaking Online Learning - Yasfin, Moh Anwar (IAIN Kudus, 2022)
Student Adjustment in Undertaking Online Learning. This study aims to reveal the Problems of Student Adjustment in Undertaking Online Learning. Research on the Problems of Student Adjustment in Undertaking Online Learning was carried out using a qualitative approach with the type of field research with data collection techniques using Interview, Observation and Documentation Techniques. The research subjects or informants in this research are students and lecturers of IAIN Kudus. The results showed that when they first took online lectures, students could not adapt because they had not found a way to make this lecture not boring. However, with the passage of time and have gotten used to learning online at home. The form of student adaptability in undergoing lectures from always being active to being absent online, listening, and responding to material in every online lecture. In addition, there are also students who have not been able to adapt to undergoing online lectures, because online lectures only look at cellphones and laptops and without any interaction between friends or with lecturers, besides that students feel that for some courses there must also be practice and direct explanations from the lecturer.Keywords: Adjustment, Student, Online Learning